MENENGOK KEMBALI PERAN AGAMA DI RUANG PUBLIK - M. Amin Abdullah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
In recent years, especially over the past decade, there has been increasing intolerance of certain religions and ethnic minorities in various parts of Indonesia, whether in the form of physical assault by a particular group or omission by the authorities. Such situation is increasing when entering the campaign period before the elections simultaneously and Presidential Election. In this condition the role of FKUB as one of the tolerant agents in the national political arena becomes important. Some things to be considered include the basic question of the State (four pillars), religious views, religious literacy and education in public spaces and media.Keywords: toleransi, pandangan keagamaan, media, ruang publik